Simulasi Interaktif Tata Surya Menggunakan Scratch sebagai Media Pembelajaran Berbasis Teknologi: Simulasi Interaktif Tata Surya Menggunakan Scratch sebagai Media Pembelajaran Berbasis Teknologi - annisa sastra_alam; jumhai ratun; hairun nisah; nur fitrianingsih (Universitas Aisyiyah Surakarta, 2026)
Background: The advancement of information technology provides significant opportunities to create more engaging and interactive learning media. Objective: This article discusses the development of an Interactive Solar System Simulation application using the Scratch platform, transformed into a web-based format using HTML, CSS, and JavaScript, to visualize planetary motion and provide a richer learning experience. Method: Development was carried out using a block-based programming approach on Scratch, subsequently converted to a web application. Results: The application successfully displays a planetary simulation, simulation control features, and interactive features such as an information monitor and a question input box, all accessible via a web browser. Conclusion: The application runs effectively and serves as an alternative learning medium for visually understanding the solar system.